Air Distributor Designs for Fluidized Bed Combustors: A Review - Ahmmad Shukrie, Md Yudin; Shahrani, Anuar; A. N., Oumer (ETASR, 2016)
Fluidized bed combustion (FBC) has been recognized as one of the suitable technologies for converting a wide variety of biomass fuels into energy. One of the key factors affecting the successful operation of fluidized bed combustion is its distributor plate design. Therefore, the main purpose of this article is to provide a critical overview of the published studies that are relevant to the characteristics of different fluidized bed air distributor designs. The review of available works display that the type of distributor design significantly affects the operation of the fluidized bed i.e., performance characteristics, fluidization quality, air flow dynamics, solid pattern and mixing caused by the direction of air flow through the distributors. Overall it is observed that high pressure drop across the distributor is one of the major draw backs of the current distributor designs. However, fluidization was stable in a fluidized bed operated at a low perforation ratio distributor due to the pressure drop across the distributor, adequate to provide uniform gas distribution. The swirling motion produced by the inclined injection of gas promotes lateral dispersion and significantly improves fluidization quality. Lastly, the research gaps are highlighted for future improvement consideration on the development of efficient distributor designs.